Pengembangan E-Modul Berbasis SETS (Science, Environment, Technology, and Society) Pada Materi Inovasi Teknologi Biologi untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X SMA/MA - Zahrah, Thifal; Idramsa; Lubis, Khairiza (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the validity, teacher responses, student responses, practicality, effectiveness, and the improvement of critical thinking skills through the development of a SETS-based. This study employed a Research and Development (R&D) approach using the 4D model. The results show that: (1) The validity of the SETS-based e-module is categorized as very feasible, with an average score of 85% for material validation, 95% for media validation, and 89% for language validation, indicating that the e-module is suitable for instructional use. (2) Teacher responses indicate that the SETS-based e-module helps students develop more comprehensive and contextual thinking, the average score obtained for the model design aspect was 85%, the concept mastery aspect was 90% and the learning motivation aspect was 88%. (3) Student responses demonstrate that the e-module meets the criteria of practicality, comfort, and usefulness, and successfully enhances learning interest and motivation. The results obtained for the module design aspect were 95%, the concept mastery aspect was 89% and the learning motivation aspect was 90%. (4) The practicality and effectiveness tests reveal an average score of 91%, placing the e-module in the highly practical and highly effective categories for learning. (5) The improvement of students’ critical thinking skills is evidenced by the t-test 0.05, which indicates a significant difference between pretest and posttest scores. The average N-Gain score of 0.758, categorized as high, shows that the SETS-based e-module increased students’ critical thinking ability by 76%. Overall, the developed SETS-based e-module is valid, practical, effective, and capable of significantly improving students’ critical thinking skills.